2009
DOI: 10.1038/hdy.2009.80
|View full text |Cite|
|
Sign up to set email alerts
|

Negative phenotypic and genetic associations between copulation duration and longevity in male seed beetles

Abstract: Reproduction can be costly and is predicted to trade-off against other characters. However, while these trade-offs are well documented for females, there has been less focus on aspects of male reproduction. Furthermore, those studies that have looked at males typically only investigate phenotypic associations, with the underlying genetics often ignored. Here, we report on phenotypic and genetic tradeoffs in male reproductive effort in the seed beetle, Callosobruchus maculatus. We find that the duration of a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 63 publications
2
21
1
Order By: Relevance
“…A more recent study found the opposite result, with significant dam effects on copulation duration (although they did give H 2 or h 2 estimates), but no effect of father genotype [45]. Our estimates of the heritability of mating duration are at the lower end of those generally found in other species ( h 2  = 0.58 in Onthophagus taurus [17], 0.39 in Scatophagia stercoraria [46], 0.26–0.36 in Callosobruchus maculatus [47]), although these studies investigated narrow-sense heritability, and so may not be directly comparable with our broad-sense heritability estimates.…”
Section: Discussioncontrasting
confidence: 85%
“…A more recent study found the opposite result, with significant dam effects on copulation duration (although they did give H 2 or h 2 estimates), but no effect of father genotype [45]. Our estimates of the heritability of mating duration are at the lower end of those generally found in other species ( h 2  = 0.58 in Onthophagus taurus [17], 0.39 in Scatophagia stercoraria [46], 0.26–0.36 in Callosobruchus maculatus [47]), although these studies investigated narrow-sense heritability, and so may not be directly comparable with our broad-sense heritability estimates.…”
Section: Discussioncontrasting
confidence: 85%
“…Ejaculate size increases with copulation duration and contributes to male reproductive success because it increases female fecundity [44]. Males that are able to copulate for longer and/or produce larger ejaculates would increase their reproductive fitness but suffer a longevity cost [38]. Selection for male longevity might lead to selection on other traits, such as locomotory behaviour, metabolic rate and metabolic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Males constantly search for mates, attempt to mount resistant females [32] and may invest up to 10 per cent of their body weight in a single copulation [37]. Reproductive effort in male seed beetles is so costly that duration of a single copulation is phenotypically and genetically correlated with reduced survival [38]. Furthermore, males have to be persistent in order to achieve matings with previously mated females [32], which is expensive in terms of energy and water.…”
Section: Resultsmentioning
confidence: 99%
“…[51] who found males exposed to thermal stress during development transferred fewer sperm but spent longer in copula than males reared under optimal conditions. Taken together, these studies indicate copulation duration to be negatively related to male quality in C. maculatus and could account for the negative phenotypic and genotypic association between copulation duration and longevity found in this species [47]. However, the relationship between copulation duration and ejaculate size is clearly a complex one as Edvardson & Canal [16] and van Leishout et al .…”
Section: Discussionmentioning
confidence: 93%
“…[52] report ejaculate weight to increase with increasing copulation duration, while Savalli & Fox [20] and Brown et al . [47] found no relationship. The upshot of these conflicting results is that caution should be exercised when interpreting the adaptive value of extended copulation without detailed knowledge of its relationship with sperm and ejaculate transfer.…”
Section: Discussionmentioning
confidence: 99%